A PHILOSOPHICAL RE-APPRAISAL OF TEACHER EDUCATION AND VALUE RE-ORIENTATION IN NIGERIA: PROGNOSIS FOR UTOPIAN SOCIETY - Oyewumi, Kassim A. (Sokoto Educational Review, 2018)
This paper deals with the re-appraisal of Teacher Education and value re-orientation as they affect Nigeria educational system. Especially on the quality of teachers who implement government policies on education. References were made to good old days in Africa when morality, honesty and sincerity pervade everywhere unlike now that foreign culture has bastardized our value. The concept of value and value re-orientation was revisited to ascertain what is acceptable to Africans as a group of people which their education process should reflect.